Implementation of Reading Spaces through Community Literacy Movement Activities in the Quran Learning Center of Tambun Selatan Village - Khasanah, Fata Nidaul; Untari, Dhian Tyas; Zahra, Fina; Ramadhani, Bianca Salikha; Khofifah, Siti Nur (PT Inovasi Pratama Internasional, 2024)
The Community Literacy Movement is an initiative aimed at strengthening lifelong learning awareness by utilizing the collective abilities of the community. A reading corner is an example of using a small space to make books more accessible and encourage interest in reading. Establishing a reading corner offers wide-ranging benefits, as it is expected to stimulate the community's interest in reading. The partner for this initiative is the Quran Learning Center (TPA) in Tambun Selatan. The challenges faced by the partner include the lack of dedicated infrastructure to promote a reading culture and a shortage of reading materials as basic literacy resources. These factors contribute to the low literacy culture in the area. The proposed solution involves transforming a room into a reading corner by providing the necessary infrastructure to support literacy activities. Additionally, training sessions will be conducted as part of a knowledge-sharing effort to provide information on the use of information technology to enhance learning activities at the TPA. Overall, the partner has found the proposed program beneficial, with the evaluation survey results showing a 100% satisfaction rate.